GENES CONFERRING ANTIMICROBIAL-RESISTANCE AMONG KLEBSIELLA PNEUMONIAE IN THE ARABIAN GULF COUNTRIES: A SYSTEMATIC REVIEW AND META-ANALYSIS - BINDAYNA, KHALID MUBARAK; JOJI, RONNI MOL; EZZAT, HICHAM; JAHRAMI, HAITHAM ALI (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The objective of the study was to look on the prevalence of six AMR genes (CTX-M, TEM, SHV, NDM-1, OXA-48, and VIM genes) in the province of the Arabian Gulf. We performed a systematic review and meta-analysis of the published studies from the Arabian Gulf countries and analyzed the antimicrobial resistance (AMR) genes pattern present in Klebsiella pneumoniae. Methods: The present study used the Meta-analysis Of Observational Studies in Epidemiology as a guideline for reporting findings. An electronic search was conducted in online databases such as PubMed/MEDLINE, EMBASE, Scopus, Google Scholar, Science Direct, and Web of Science from January 2014 to June 2020 following the inclusion and exclusion criteria. Articles published were included in the study resistance pattern among 2036 isolates were analyzed. These isolates conferred the AMR genes including OXA-48 (n=500), CTX-M (n= 1796), SHV (n=1637), TEM (n=1492), NDM-1 (n=500), and VIM (n=302). Results: Of 160 initially searched studies, 28 entries met the inclusion criteria and were subjected to meta-analysis. Critical appraisal of studies or quality assessment revealed a mean quality score was 4.2, with an SD of 1.6. The analysis revealed predominant AMR genes wereOXA-48 followed by CTX-M, SHV, TEM, NDM-1, and VIM in the Arabian Gulf region. Conclusion: The Arabian Gulf countries share a high prevalence of OXA-48, CTX-M followed by SHV, TEM, NDM-1, and VIM genes. Antimicrobial-resistant in K. pneumoniae is a threat to public health and this needs strong surveillance to curb this threat.